2018
DOI: 10.1021/acsomega.7b02009
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field-Induced Dynamic Electronic Junctions in Hybrid Organic–Inorganic Perovskites for Optoelectronic Applications

Abstract: Organic–inorganic metal halide perovskites have attracted great attention as optoelectronic materials because of their low cost, relative insensitivity to defects, and solution-processible properties. However, some of their properties, such as thermal instability, toxicity, and current–voltage hysteresis still remain elusive. Ion migration, which has been proven to be a thermal-activated process, is regarded as one of the major origins of the hysteresis and thus detrimental to the long-term stability of the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The new understandings of the ion-migration in the lead-free halide double perovskites can promote designing strategies for further materials and device stability improvement. Despite the adverse influence on the stability, it's noted that the ion-migration phenomenon in the metal halide perovskites is a "double-edged sword," which has been found to facilitate the fast response in photodetectors by forming dynamic electronic junctions [48,49] and also demonstrate important applications in resistance-switching memory devices [50][51][52] and artificial synapses. [53]…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…The new understandings of the ion-migration in the lead-free halide double perovskites can promote designing strategies for further materials and device stability improvement. Despite the adverse influence on the stability, it's noted that the ion-migration phenomenon in the metal halide perovskites is a "double-edged sword," which has been found to facilitate the fast response in photodetectors by forming dynamic electronic junctions [48,49] and also demonstrate important applications in resistance-switching memory devices [50][51][52] and artificial synapses. [53]…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…The ions redistribution would induce an internal electric field inside the optoelectronic device. [ 39,40 ] Notably, it has been reported that the ion‐redistribution‐triggered p–i–n junction leads to the increased open‐circuit voltage and short‐circuit current of solar cells. [ 16,25 ] Here, either the internal electric field or the p–i–n junction does not contribute to the enhanced photocurrents of the MAPbBr 3 ‐film‐based photodetector in this work due to the following two reasons.…”
Section: Figurementioning
confidence: 99%
“…Moreover, ion migration has found important application in perovskite resistance‐switching memory devices . Finally, by manipulating the ion migration progress under different electric field, dynamic electronic junctions are demonstrated and can be used as fast response photodetectors . Therefore, understanding and manipulating of the ion migration process in HOIP materials, which has been a formidable challenge, holds the key for developing “state of the art” perovskite devices.…”
Section: Introductionmentioning
confidence: 99%